Exploring students’ challenges in using AI to complete their intensive reading projects - Susanti Malasari; Paulina Besty Fortinasari; Bintang Nugroho; Nurul Hidayati (English Learning Innovation, 2026)
In the context of Intensive Reading class, AI can help students look for reading texts, giving information about pronunciation and intonation when reading texts, determining main idea and understanding the content of texts. Besides, AI can also help students finish Intensive Reading task-based projects that require creative ideas and in-depth analysis. However, the use of AI to finish task-based projects in Intensive Reading class can cause various challenges for students. Therefore, this research explores the students’ challenges in using AI to complete their intensive reading projects. This research is qualitative in nature. It employed 25 students from intensive Reading Class. The results reveal that in completing project-based assignments in the Intensive Reading class, students use AI to get detailed explanation related to the topic, paraphrase sentences that they cited, summarize long texts, find relevant information to the assignment given by the lecturer, build frameworks, develop ideas, and improve grammar in elaborating the intensive reading projects. The study also reveals the challenges faced by students when using AI to complete their projects. These challenges include the occasional irrelevance of AI generated information, students’ dependence on AI, a decline on critical thinking skill, and the potential for plagiarism. The findings highlight the need to create clear guidelines of using AI in Intensive Reading Class. In addition, lecturers need to provide class activities that can boost students’ critical thinking to ensure that AI is only used as a supporting tool in the teaching and learning process.